PERANCANGAN APLIKASI PERAMALAN STOK GUDANG MENGGUNAKAN METODE MOVING AVERAGE - latipah latipah (Universitas Narotama, 2020)
This study aims to design a warehouse stock forecasting application using the moving average method with a 3 month moving average value. Stock forecasting is done to balance the stock in the warehouse so that it is not excessive and not less, Sale of good sold is on target and consumers don’t switch to competitors which result in losses to the company. Moving Average method used in this study due to sales data have a random pattern. The first step in calculating the Moving Average method in designing the system is to take sales data from 12 months before the forecasting period. Next, calculate forecasting using data of 3 months. As results, we will note the smallest Mean Absolute Percent Error (MAPE) and the moving average every month. Forecasting with smallest MAPE value will be shown to system users. The final result of this system design is that the moving average method can be used to predict the stock of goods, but not all forecasting has good results because of the large amount of data and varied patterns. Therefore, in every forecasting must be include forecast error for consideration of decision making